PENGARUH PROFITABILITAS, LEVERAGE, DAN LIKUIDITAS TERHADAP KETEPATAN WAKTU PENYAMPAIAN LAPORAN KEUANGAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA 2022-2024) - Tiara Asrini; Tiara Arnadi Chairunnas; Sasmita Nabila Syahri; Bustang Bustang (Jurnal Akuntansi Kompetif, 2026)
This study was conducted to analyze the impact of profitability, debt structure (leverage), and liquidity on compliance with financial reporting publication deadlines. This study employed a quantitative research design, drawing samples using a purposive sampling method. Twenty manufacturing entities listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period were selected as samples, resulting in 60 observation units. Hypothesis testing was conducted using logistic regression. Empirical findings indicated no significant impact of profitability on reporting discipline. Leverage, on the other hand, played a significant role in encouraging precise publication, while liquidity exerted an influence at the 10% significance level. When tested simultaneously, these three financial indicators were shown to significantly influence compliance with reporting deadlines. Keywords: Profitabilitas, Leverage, Likuiditas, Timeliness, Financial Reporting